2010
DOI: 10.1111/j.1751-228x.2009.01081.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Context on the Development of Aggressive Behavior in Special Elementary School Children

Abstract: The role of context in the development of child aggression was studied. The effects of peer aggregation and group composition on aggression development in intervention contexts and classroom contexts were compared using 71 elementary school children. We hypothesized that, due to peer group effects, group‐trained children would benefit less from a social skills intervention program than individually trained children. We further hypothesized that children who transferred from special to regular education would s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…The increased aggression levels among retained students may reflect feelings of frustration regarding their decreased academic status, as well as increased peer relationship challenges faced by students after grade retention. Some research suggests that placement in special education classes is also linked to the escalation of aggressive behavior due to peer contagion (Visser, Kunnen, & Van Geert, 2010), although not all studies find this negative impact (White & Loeber, 2008). …”
Section: Developmental Processes Associated With Early Aggression Andmentioning
confidence: 99%
“…The increased aggression levels among retained students may reflect feelings of frustration regarding their decreased academic status, as well as increased peer relationship challenges faced by students after grade retention. Some research suggests that placement in special education classes is also linked to the escalation of aggressive behavior due to peer contagion (Visser, Kunnen, & Van Geert, 2010), although not all studies find this negative impact (White & Loeber, 2008). …”
Section: Developmental Processes Associated With Early Aggression Andmentioning
confidence: 99%
“…Similarly, research within clinical settings suggests that the composition of group interventions is related to treatment outcomes and can predict either positive or negative behavior (e.g., Dodge et al, 2006). Thus, the social dynamics within EBD classrooms are not inherently deleterious, as other research has suggested (Müller, 2010;Visser et al, 2010). Rather, the influence of classroom behavior norms within EBD settings is similar to that within mainstream settings.…”
Section: Third Research Question: Role Of Classroom Normsmentioning
confidence: 82%
“…Group composition is closely related to behavior norms as the distribution of individuals with specific behaviors at the formation of a group influences norm development (Laninga-Wijnen et al, 2018;Müller, 2010). As such, the terms group composition and behavior norms have occasionally been used interchangeably (Visser et al, 2010). Research findings consistently demonstrate that as the ratio of antisocial/disruptive youth in an intervention group increases, the effectiveness of the intervention tends to decrease (Ang & Hughes, 2002;Macgowan & Wagner, 2005).…”
Section: Peer Influence In Interventionsmentioning
confidence: 99%
“…The statistical procedures consisted of descriptive analyses performed in Microsoft Excel and permutation tests using Monte Carlo analysis (Good, 1999; Todman & Dugard, 2001) performed in Poptools (Hood, 2008). For a detailed example, see Visser, Kunnen, and Van Geert (2010). Each significance test was based on 1,000 simulations.…”
Section: Methodsmentioning
confidence: 99%